Efficacy and safety of histone deacetylase inhibitors in peripheral T-cell lymphoma: a systematic review and meta-analysis on prospective clinical trials - Yang, Peipei; Tao, Yali; Zhao, Ailin; Shen, Kai; Li, He; Wang, Jinjin; Zhou, Hui; Wang, Zhongwang; Wang, Mengyao; Qu, Ying; Zhang, Li; Zheng, Yuhuan; et al. (Frontiers in Oncology, 2023)
Background: The overall survival of peripheral T-cell lymphoma (PTCL) is dismal. Histone deacetylase (HDAC) inhibitors have exhibited promising treatment outcomes for PTCL patients. Therefore, this work aims to systematically evaluate the treatment outcome and safety profile of HDAC inhibitor-based treatment for untreated and relapsed/refractory (R/R) PTCL patients. Methods: The prospective clinical trials of HDAC inhibitors for the treatment of PTCL were searched on the Web of Science, PubMed, Embase, ClinicalTrials.gov, and Cochrane Library database. The pooled overall response rate, complete response (CR) rate, and partial response rate were measured. The risk of adverse events was evaluated. Moreover, the subgroup analysis was utilized to assess the efficacy among different HDAC inhibitors and efficacy in different PTCL subtypes. Results: For untreated PTCL, 502 patients in seven studies were involved, and the pooled CR rate was 44% (95% CI, 39-48%). For R/R PTCL patients, there were 16 studies included, and the CR rate was 14% (95% CI, 11-16%). The HDAC inhibitor-based combination therapy exhibited better efficacy when compared with HDAC inhibitor monotherapy for R/R PTCL patients (P = 0.02). In addition, the pooled CR rate was 17% (95% CI, 13-22%), 10% (95% CI, 5-15%), and 10% (95% CI, 5-15%) in the romidepsin, belinostat, and chidamide monotherapy subgroups, respectively. In the R/R angioimmunoblastic T-cell lymphoma subgroup, the pooled ORR was 44% (95% CI, 35-53%), higher than other subtypes. A total of 18 studies were involved in the safety assessment of treatment-related adverse events. Thrombocytopenia and nausea were the most common hematological and non-hematological adverse events, respectively. Conclusion: This meta-analysis demonstrated that HDAC inhibitors were effective treatment options for untreated and R/R PTCL patients. The combination of HDAC inhibitor and chemotherapy exhibited superior efficacy to HDAC inhibitor monotherapy in the R/R PTCL setting. Additionally, HDAC inhibitor-based therapy had higher efficacy in angioimmunoblastic T-cell lymphoma patients than that in other subtypes.